ANALISIS RISIKO USAHA KOPRA DI DESA BUKIT TINGI KEC KAKAS BARAT KABUPATEN MINAHASA - Feren Fidelya Pantow; Allen Ch. Manongko; Silvana Oroh (Literacy: Jurnal Pendidikan Ekonomi, 2024)
< StartFragment > ABSTRACT< span>< strong>< p> This study aims to describe the Analysis of Coconut Business Risks in Bukit Tinggi Village Kakas Barat Sub District Minahasa District The research method used is descriptive method using qualitative data Data collection techniques were carried out through observation interviews and literature study Data analysis methods were carried out starting from data collection data reduction data presentation and drawing conclusions Based on the results of interviews with coconut business actors in Bukit Tinggi Village several risk management strategies appear to be central to their business operations Coconut business actors strive to create a solid foundation to overcome potential risks They understand the importance of adaptability partnerships and risk transfer in maintaining the sustainability of coconut businesses in Bukit Tinggi Village < span>< p> < EndFragment >< li> < ul>